(untitled) (Indian Journal of Public Health Research & Development, 2020)
Application of computer-aided impression procedures are preferable to conventional impression procedures for Implant supported prosthesis. Data about the accuracy of the digital impression-making technologies in comparison to the conventional ones is scarce. This meta analysis is an attempt to decipher the preferred method of impression making of implant superstructures by analyzing data about these two impression making procedures.